2018
DOI: 10.1001/jama.2018.13467
|View full text |Cite
|
Sign up to set email alerts
|

Association of Clinical and Social Factors With Excess Hypertension Risk in Black Compared With White US Adults

Abstract: The high prevalence of hypertension among the US black population is a major contributor to disparities in life expectancy; however, the causes for higher incidence of hypertension among black adults are unknown. OBJECTIVE To evaluate potential factors associated with higher risk of incident hypertension among black adults. DESIGN, SETTING, AND PARTICIPANTS Prospective cohort study of black and white adults selected from a longitudinal cohort study of 30 239 participants as not having hypertension at baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(82 citation statements)
references
References 37 publications
1
78
2
1
Order By: Relevance
“…This could be related to imprecise measurement of adiposity and vascular health and/or the low rates of CVD. Additionally, racial disparities in CVD have been related to neighborhood conditions, access to and quality of medical care, and lifestyle behaviors, such as poor diet (Chin et al, 2011;Howard et al, 2018). These are variables that need to be included in future research to obtain a holistic understanding of racial disparities as it relates to CVD and brain aging, in general, and to CTE and related disorders, in particular.…”
Section: Discussionmentioning
confidence: 99%
“…This could be related to imprecise measurement of adiposity and vascular health and/or the low rates of CVD. Additionally, racial disparities in CVD have been related to neighborhood conditions, access to and quality of medical care, and lifestyle behaviors, such as poor diet (Chin et al, 2011;Howard et al, 2018). These are variables that need to be included in future research to obtain a holistic understanding of racial disparities as it relates to CVD and brain aging, in general, and to CTE and related disorders, in particular.…”
Section: Discussionmentioning
confidence: 99%
“…One systematic review of multi-ethnic cohort studies concluded that dementia incidence rates are higher in African Americans and Hispanics compared to non-Hispanic Whites ( Mehta and Yeo, 2017 ). Some have argued that these observed disparities are due to a multitude of related factors, including increased prevalence of cardiovascular conditions, lower education and socioeconomic status, barriers to health care, and certain lifestyle factors ( Judd et al, 2013 ; Diaz-Venegas et al, 2016 ; Howard et al, 2018 ; Weuve et al, 2018 ). With limited treatments to reverse memory loss or dementia, the identification of modifiable risk factors are of great public health interest.…”
Section: Introductionmentioning
confidence: 99%
“…The relation between blood pressure (BP) and several nutrients abundant in UPF has been established. Indeed, intakes of salt, sugar-sweetened beverages, and diets rich in fat and sugar are associated with increased risk of hypertension [22][23][24][25]. To date, only two studies have specifically investigated the effects of UPF on cardiovascular health.…”
Section: Introductionmentioning
confidence: 99%